Implementasi Knowledge Management pada UMKM Indonesia Untuk Meningkatkan Daya Saing UMKM dalam Dunia Internasional - Setiadi Umar (Jurnal Siasat Bisnis, 2008)
It is indisputable that SMEs (Small Medium Enterprises) hold a key role in Indonesian Economic Development. Steps should be taken to increase the performance of SMEs and thus its contribution to the Indonesian economy, since a 10% increase in SMEs performance could mean a 5% increase in Indonesian GDP.  This is a significant number, remembering our GDP only increases by an average of 6% per annum. According to strategic management experts, the ability of one company to make an economic profit (an above average level of profit) depends on their ability to compete. Many pilot projects that conducted have failed and met enormous obstacles along the way. This research analyzes and highlights the condition of Innovation actors in Indonesia, who implement the knowledge management and problems in implementing knowledge management in Indonesia’s environment. Therefore, it is hoped that strategic solutions can be proposed. Keywords:    implementation knowledge management, inovation, aktor inovasi Indonesia, UMKM, daya saing UMKM